13y+6=12y+16

Simple and best practice solution for 13y+6=12y+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13y+6=12y+16 equation:


Simplifying
13y + 6 = 12y + 16

Reorder the terms:
6 + 13y = 12y + 16

Reorder the terms:
6 + 13y = 16 + 12y

Solving
6 + 13y = 16 + 12y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-12y' to each side of the equation.
6 + 13y + -12y = 16 + 12y + -12y

Combine like terms: 13y + -12y = 1y
6 + 1y = 16 + 12y + -12y

Combine like terms: 12y + -12y = 0
6 + 1y = 16 + 0
6 + 1y = 16

Add '-6' to each side of the equation.
6 + -6 + 1y = 16 + -6

Combine like terms: 6 + -6 = 0
0 + 1y = 16 + -6
1y = 16 + -6

Combine like terms: 16 + -6 = 10
1y = 10

Divide each side by '1'.
y = 10

Simplifying
y = 10

See similar equations:

| 2+1/2=1+1/4(x-2) | | 312=16t^2 | | 4(1-8)+10=-10 | | 2/1/2=1+1/4(x-2) | | 21/2=1+1/4(x-2) | | 0.05z+0.1(2z)+0.25(100-3z)=20 | | 7x-19=6x-19 | | 2x-8x-11=-6x+2-11 | | 3x+2=3x+2 | | 14-|-20|= | | (n^2-n-70)=0 | | -6x-16=3x+11 | | 9(x-2)+7=6x+3(-2+x) | | y=x^2+7 | | 8x+11-x=31 | | x^2-x-1=(x+5)(x+5) | | 10x+32=4(2x+9)+2x-4 | | 12x+15=21 | | -3(4t-4)+6t=2t-5 | | 35+(-27)(-3)= | | s=5k+5v | | -2(t+3)=9-5t | | x+3/2=3/4(x-.5) | | 45x-9=34x-2 | | -9-x=x+5 | | 37=2x+-36 | | 0.26=log(x) | | -6+c=82 | | -7+32-12+5= | | 9x+8=x-11 | | -6+y(-23)=82 | | 3x^2-81=12 |

Equations solver categories